Paisagem e geoecologia : enfoques geoecológicos em apoio ao estudo das paisagens na sub-bacia hidrográfica do rio Sucuru, alto curso do Paraíba, PB - Rodrigues, José Marcos Duarte (2023)
Geoecological studies consist of a system of research methods, procedures and techniques that provide knowledge about the natural and anthropo-natural environments. Based on this statement, this research aims to analyze landscapes using geoecological approaches and determine the functional state of the Sucuru River sub-basin, that is the upper course of the Paraíba River, State of Paraíba. This area has 1.681 km² and it is located in the mesoregion of Borborema, a microregion of Western Cariri. Therefore, at first, we looked to identify multiple definitions and perspectives of the concept of landscape in Geographical Science from the initial conceptions to the resumption of Landscape Studies in the twentieth century. Subsequently, we looked to understand the geoecology of landscapes as a theoretical-methodological approach, analyzing its origins and development, distinguishing the geographical perspective from the ecological to then deepen the approach adopted in the research. Following, we analyzed the components forming landscapes, geology, geomorphology, climate and water resources, soil classes and land usage and cover, interpreting them as a unity belonging to the whole. Then, the geoecological units of landscapes were regionalized and typified, and the regions were distinguished according to predominant morphogenetic processes (denudational) and subdivided according to their analogous traits in different landscape units. Afterward, the analysis of the landscape units were guided based on geoecological approaches; its components and interrelation, its functional structure, genesis and evolution, the historical process of usage and occupation, population dynamics and degrading activities were analyzed to establish their functional state. Thus, it is concluded that the landscapes that make up the Sucuru River sub-basin are like a heterogeneous mosaic, composed of natural and anthropic components that attribute their own particularities. They are in varied functional states, presenting modifications in their structural organization and imbalances in their functionality. In such wise, this paper intends to contribute both to further research and to society in general.